Disulfide bond formation in the eye lens. - Yu, N T (1985)
The disposition and disposal of the -SH groups of the lens during aging and cataractogenesis have been investigated by laser Raman spectroscopy as a noninvasive microprobe in the intact living lens. In this procedure -SH and -S-S- give unique discrete Raman signals (at 2580 and 508 cm-1) that may be used to calculate relative concentrations in a very small volume of the lens. We present evidence showing an unexpected and remarkable difference with respect to these groups between the mouse lens and the lenses of guinea pig and man. The mouse lens nucleus exhibits a precipitous fall in the -SH concentration on aging from 1 to 6 months; concomitantly, there is a rise in -S-S- of comparable magnitude, indicating a direct conversion. The guinea pig lens, however, is quite different with respect to the age-dependent change in nuclear -S-S-: there is none between 6 months and 5 years. In the human lens -S-S- behaves exactly as in the guinea pig lens: the level is low and does not change with age between 9 and 65 years. With respect to nuclear -SH, these two latter species of lenses show some decrease with age but nothing like the approach to zero found in the aging mouse lens nucleus. These differences involving lenticular -SH and -S-S- appear to be correlated with the hard nucleus in the mouse lens and the softer nuclei of lenses in guinea pigs and humans. The relatively high level of -S-S- in the old but clear mouse lens does not support the idea that protein aggregation involving formation of intermolecular -S-S- bonds is necessarily an important cause of nuclear cataract. The small but significant age-related depression of -SH in guinea pig lens nuclei without any accumulation of -S-S- may be explained as a result of glutathione (GSH) oxidation and subsequent extrusion of glutathione disulfide (GSSG) by the lens. We propose that the oxidation of glutathione proceeds by reaction with protein disulfide groups to yield protein sulfhydryl (PSH) and a mixed disulfide of glutathione and protein; the mixed disulfide is capable of being reduced by glutathione reductase and NADPH, yielding the original PSH and GSSG, which is extruded from the lens. It remains to be determined if this mechanism is more active in guinea pig and human lenses than in the mouse lens.